PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII D SMP NEGERI 9 PALU PADA MATERI SEGITIGA: Application Of The Guided Discovery Learning Model To Improve The Learning Outcomes Of Clas VIII D Students at SMP Negeri 9 Palu On Triangle Material - Bago, Kiswanda; Sukayasa; Rizal, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to describe the application of the guided discovery learning model in improving the learning outcomes of class VII D students of SMP Negeri 9 Palu on triangle material.Based on the results of the final action test, the percentage of students 'classical learning completeness in cycle I was 64.28% and the percentage of students' classical learning completeness in cycle II was 92.59%, while the results of teacher and student observations in cycle I were in the good category and at cycle II is in the very good category. Based on the results of the study, it can be concluded that learning by applying the guided discovery learning model can improve the learning outcomes of grade VII students of SMP Negeri 9 Palu in triangular material by following the steps (1) stimulation: giving students an explanation of the triangular material contained in LKPD. (2) problem formulation: directing students to find their own triangle material by asking students to observe and identify the problems contained in the LKPD and make hypotheses. (3) data collection: students are asked to look for references related to triangular material, then write down the information contained in the given problem carefully. (4) data processing: after data collection, further data processing is required, students process the data that has been collected by discussing the process used to find problems in the LKPD. (5) verification: students are asked to formulate conclusions and then match them with the formulation of the problem given whether the formulation of the conclusions made answers the given problem and whether the results obtained are in accordance with the hypotheses made have been proven or not. and (6) generalization: involving students in class discussions and concluding the material that has been studied.